New insights on interpretation of velocity anomalies in the offshore Nile Delta basin, Egypt - Hanafy, Said; Nimmagadda, Shastri; Mahmoud, Sharaf Eldin; Mabrouk, Waleed (SPRINGER HEIDELBERG, 2020)
© 2020, Saudi Society for Geosciences. Several issues associated with existing velocity models and their anomalies affecting the petroleum geology of the offshore Nile Delta basin are described. The paper aims to present velocity and pressure variations and their associated pitfalls in the deeper Nile Delta, where the ambiguities exist in the interpretation of depth structures, especially in between sea bottom and Oligocene sequences. Different conceptualized geological, velocity, and seismic models are generated. We make use of data cubes to generate data views for geological interpretation. The connectivity is established between velocity anomalies and corresponding seismic times, ascertaining that the depth structures have geological implications. The visualization of representative schematic data views of velocity anomalies facilitates the interpretation of new knowledge and the connectivity between seismic and geological models. The velocity attributes significantly influence the seismic data interpretation in the offshore Nile Delta basin and have an impact on the overall cycle of the exploration and production entities.